2019
DOI: 10.3892/mco.2019.1870
|View full text |Cite
|
Sign up to set email alerts
|

An updated review of mucosal melanoma: Survival meta‑analysis

Abstract: Mucosal melanoma (MM) is a highly lethal variant of melanoma that carries a poor prognosis. Extremely low incidence and survival rates have led to few clinical trials, and a lack of protocols and guidelines. The present study performed a survival meta-analysis for the quantitative synthesis of available evidence to search for key patterns that would help clinicians tailor optimal therapeutic strategies in MM. PubMed, EMBASE, Cochrane, MEDLINE, Google Scholar and other databases were searched. Hazard ratios, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
2
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 70 publications
0
31
2
2
Order By: Relevance
“…15 Male gender, tumour thickness, age, ulceration and advanced tumour stage at initial diagnosis are linked to a less favourable prognosis for mucosal melanoma. [14][15][16][17][18][19][20][21] In the current study, age ≥60, anorectal localization, thickness and advanced tumour stage were identified as significant negative prognostic factors for survival according to the univariate analysis. In the multivariate analysis, older age and advanced tumour stage remained independent significant influence factors for survival.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…15 Male gender, tumour thickness, age, ulceration and advanced tumour stage at initial diagnosis are linked to a less favourable prognosis for mucosal melanoma. [14][15][16][17][18][19][20][21] In the current study, age ≥60, anorectal localization, thickness and advanced tumour stage were identified as significant negative prognostic factors for survival according to the univariate analysis. In the multivariate analysis, older age and advanced tumour stage remained independent significant influence factors for survival.…”
Section: Discussionmentioning
confidence: 60%
“…[11][12][13] In a recent meta-analysis, mucosal melanomas are shown to be 2.25 times more lethal than cutaneous melanomas. 14 The reported survival rates for mucosal melanoma vary depending on the anatomical localization. The overall 5-year survival rate for mucosal melanoma is calculated to be 0-45%.…”
Section: Discussionmentioning
confidence: 99%
“…For similar reasons, patient survival is higher in this type of melanoma than in the non-cutaneous counterparts because of earlier diagnosis. For instance, a recent meta-analysis showed a 2.25-fold higher lethality in mucosal than in cutaneous melanoma [31]. The overall survival (OS) and disease-specific survival (DSS) in melanoma patients depends on many factors including tumor stage, histology, type of treatment the patient is receiving, as well as age [32].…”
Section: Staging Of Melanoma and Patient Survivalmentioning
confidence: 99%
“…Due to the difficulties with diagnosis, the complicated anatomical location and the infrequency, there have been no large randomized control trials to evaluate for the best treatment approach (although in development) [5]. The five-year survival rate is 25% [6].…”
Section: Introductionmentioning
confidence: 99%
“…Nivolumab, a humanized monoclonal antibody that blocks PD-1; cell check point inhibitor, also results in increased T-cell function. Due to the novel and differing mechanism of actions, both of these immunotherapies work in concert and independently to attack the tumor cells [ 4 - 5 ].…”
Section: Introductionmentioning
confidence: 99%